Results of primary hip endoprosthesis replacement at fractures of trochanteric region of the femur in elderly patients - A. K. Dulaev; A. N. Tsed; K. N. Usubaliev; K. G. Iljushchenko; N. E. Mushtin (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2016)
To track longterm outcomes of primary total hip replacement in elderly patients with various fractures of the trochanteric region. We studied the retrospective results of surgical treatment of 62 patients with fractures of the trochanteric region of the femur, who underwent primary total hip replacement. Patients were divided into two groups. 1–58 (72.5 %) patients with stable fractures, 2–22 (27.5 %) patients with unstable fractures. The functionality results have been evaluated on Harris scale before the injury and after surgery. Satisfactory functional parameters detected in all 44 patients operated on in the first group. In the second group: satisfactory performance were observed in 16 (88.8 %) of 18 patients. The results of hip replacement in elderly patients with stable fractures pertrochanteric allow to speak about the effectiveness of this type of surgery. Endoprosthesis of transtrochanteric unstable fractures requires further study because of the extremely high frequency of postoperative complications (up 88.8 %). Reconstruction of the large and small trochanter is important to improve the biomechanics of periprosthetic fractures in transtrochanteric arthroplasty. Locking of 8shaped wire loop around the bone fragments of the large and small trochanter ensures the stability of the endoprosthesis.